Optical and Amplified Spontaneous Emission Properties of 4H-Pyran-4-Ylidene-2-Cyanoacetate Fragment Containing 2-Cyanoacetic Acid Derivative in PVK, PSU, or PS Matrix - Paulsone, Patricija; Pervenecka, Julija; Zarins, Elmars; Kokars, Valdis; Vembris, Aivars (MDPI, 2024)
Organic solid-state lasers are highly promising devices known for their low-cost fabrication processes and compact sizes and the tunability of their emission spectrum. These lasers are in high demand across various industries including biomedicine, sensors, communications, spectroscopy, and military applications. A key requirement for light-emitting materials used in a light-amplifying medium is a low threshold value of the excitation energy of the amplified spontaneous emission (ASE). A newly synthesized non-symmetric red-light-emitting laser dye, Ethyl 2-(2-(4-(bis(2-(trityloxy)ethyl)amino)styryl)-6-tert butyl-4H-pyran-4-ylidene)-2-cyanoacetate (KTB), has shown great promise in meeting this requirement. KTB, with its attached bulky trityloxyethyl groups, has the ability to form amorphous thin films from a solution using a wet-casting method. Recent experiments have demonstrated that KTB exhibits a low ASE threshold value. This study focused on investigating the optical and amplified spontaneous emission properties of KTB in poly(N-vinylcarbazole) (PVK), polysulfone (PSU), and polystyrene (PS) matrices at various concentrations. The results showed that as the concentration of the dye increased, a redshift of the photoluminescence and ASE spectra occurred due to the solid-state solvation effect. The lowest ASE threshold value of 9 µJ/cm2 was achieved with a 20 wt% concentration of KTB in a PVK matrix, making it one of the lowest excitation threshold energies reported to date. © 2024 by the authors. --//-- This is an open-access article Paulsone, P.; Pervenecka, J.; Zarins, E.; Kokars, V.; Vembris, A. Optical and Amplified Spontaneous Emission Properties of 4H-Pyran-4-Ylidene-2-Cyanoacetate Fragment Containing 2-Cyanoacetic Acid Derivative in PVK, PSU, or PS Matrix. Solids 2024, 5, 520-532. https://doi.org/10.3390/solids5040035 published under the CC BY 4.0 licence.
European Regional Development Fund (ERDF) 1.1.1.1 Activity Project Nr. 1.1.1.1/16/A/046 “Application assessment of novel organic materials by prototyping of photonic devices”. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; amorphous materials; amplified spontaneous emission; cyanoacetic acid derivative; guest–host system; molecular glass; organic laser dyes